Antibacterial Activities From Jangkang (Homalocladium platycladum (F. Muell) Bailey) Leaves - Maulita Cut Nuria (Universitas Wahid Hasyim, 2010)
Jangkang (Homalocladium platycladum (F. Muell) Bailey) is ashrub under the Polygonaceae family and grows throughout Indonesia. Thisplant has been traditionally used to relief pain, to cure skin infection and hasantiinflamatory activity. Phytochemical studies showed that this speciescontains saponin, flavonoid and tannin. The aim of this research is to findout antibacterial activities of several extract from jangkang leaves againstGram positive bacteria (Staphylococcus aureus dan Bacillus subtilis) andGram negative bacteria (Escherichia coli dan Salmonella typhi).The dried ground leaves (300.04 gram) were macerated withpetroleum ether, chloroform and methanol respectively. Petroleum ether,chloroform and methanol extracts were obtained after evaporation of thesolvents. The extracts tested for their antibacterial activities using agardiffusion method aided by paper disks in order to find out the inhibitory areadiameters.The result showed that petroleum ether extract did not inhibited thegrowth of bacteria but chloroform and metanol extracts show antibacterialactivity except at E. coli. Chloroform extract shows inhibition zone againstbacteria at concentration of 1000 μg/disk while methanol extract atconcentration of 500 μg/disk.Keywords : Jangkang (Homalocladium platycladum (F. Muell) Bailey)leaves, Antibacterial activity